Effectiveness of Oral Herbal in Postpartum and Breastfeeding - Sayuti, Nutrisia Aquariushinta; Atikah, Nur (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Health care during the postpartum and breastfeeding periods fulfils the needs of the mother and baby. 'Jamu', or herbal medicine, is often used for this purpose, but there needs to be more evidence of its effectiveness. The public's insufficient understanding of herbal medicine necessitates a systematic review to assess its contents, benefits, and side effects. The systematic review aimed to examine oral herbal medicines during puerperium or breastfeeding, using the RCT method to provide evidence of IB levels in EBM. Methods: Inclusion criteria were articles in randomised controlled trials (RCTs) to investigate the effectiveness of oral herbs during the puerperium and lactation. The methodological quality of articles was tested with the Jadad Score. Results: The five (5) selected articles have good quality (the Jadad Score was 5–8). The study tested five herbs, including fenugreek, honey, bitter fennel, Brazilian propolis, barley malt, and Thai herbal tea "Wang Nam Yean" (a mixture of sappan wood (secang), bael (maja) fruit, licorice, ginger, and tuba (Derris scandens)). Comparators included placebo and other herbs or Domperidone. Most clinical outcomes involved successful breastfeeding, but complications, infant weight gain, and side effects were also observed. Conclusion: Herbs can aid in healthy breastfeeding, but they should be taken cautiously and in conjunction with the assessment, counselling, and support of healthcare professionals. No herbal medicine has the best evidence-based practices because the evidence has not been applied to clinical practice, so changes in clinical practice results have yet to be documented.